OBSTETRIC AND GYNECOLOGICAL HISTORY OF PREGNANT WOMEN WITH CHRONIC VIRAL HEPATITIS B WITH AND WITHOUT DELTA AGENT - Tashpulatova Sh.A., (Central Asian Journal of Medicine, 2025)
The impact of infection in women suffering from chronic viral hepatitis B on pregnancy outcomes has not been fully studied, and existing research shows contradictory results. A review of the literature revealed no reliable data on the course and outcomes of hepatitis D during pregnancy. The aim of this study was to analyze the obstetric and gynecological history of pregnant women infected with chronic viral hepatitis B with and without the D-agent. From 2017 to 2021, a prospective study was conducted at the City Clinical Infectious Diseases Hospital No. 1 in Tashkent involving 260 pregnant women: 142 were infected with HBV without the D-agent, and 118 with the D-agent. The results showed that pregnant women with HBV without the D-agent had a significantly higher probability of favorable pregnancy outcomes, whereas women with HBV associated with the D-agent experienced significantly more frequent complicated deliveries and neonatal complications.